Physiological Functions of Mcl-1: Insights From Genetic Mouse Models - Chin, Hui San; Fu, Nai Yang (Frontiers in Cell and Developmental Biology, 2021)
Proteins of the Bcl-2 family is characterized by the presence of at least one of the four Bcl-2 homology (BH) domains. In mammals, this protein family consists of BH3-only (Bim, Bad, Bid, Bik, Noxa, Puma, Moap-1 and Hrk) as well as multidomain pro-apoptotic (Bak, Bax and Bok) and pro-survival members (Bcl-2, Bcl-w, Mcl-1, Bcl-XL, and A1/Bfl-1). Through physical interactions, the interplay between the pro-apoptotic and pro-survival Bcl-2 members regulates apoptosis signaling at the mitochondria. The physiological roles of distinct Bcl-2 family members are largely unmasked by genetically engineered murine models. Mcl-1 is one of the two proteins among the Bcl-2 family of protein whose germline deletion causes embryonic lethality in mice. Extensive studies on tissue- and cell type-specific gene deletion murine model systems have established the non-redundant in vivo role of Mcl-1 in a broad range of cell types. This includes hematopoietic stem cells and multiple cell lineages along their differentiation hierarchy, epithelial cells in the thymus, mammary gland and liver, cardiomyocytes, endothelial cells, neurons and oocytes. Moreover, emerging evidence suggests that human and mouse Mcl-1 protein shows differences in certain aspects. Indeed, inhibitors with high affinity and specificity to human Mcl-1 have been successfully generated. To facilitate the pre-clinical studies of Mcl-1 in cancer and other diseases, transgenic mouse models over-expressing human Mcl-1 as well as humanized Mcl-1 mouse models have been engineered. This review discusses the current advances in understanding the physiological roles of Mcl-1 based on studies using murine models and its implications in treatment of human diseases.